(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To assess the efficacy of shoulder cuff restoration by means of arthroscopic repair in dual row repair fashion and demonstrate 30 months practical result using a scoring system based on modified American Shoulder & Elbow Score System (ASES) Materials And Methods: This is a descriptive cross-sectional study and includes 23 patients who underwent repair of massive rotator cuff tears in double row manner arthroscopically. Study was carried out at Liaquat National Hospital during January 2018 June 2019 at orthopedics department. The clinical evaluation was done by the operative surgeon on the patients reported for surgery in outpatient department pre-operatively and then at follow up postoperatively at 6 weeks, 3 months, 6 months ,1 year and final evaluation done on average of 30 months. Preoperative and postoperative functional evaluation done and compared by assessing the function on basis of a scoring system based on modified ASES score Results: The average functional outcome scores based on Patient Self Assessed Questionnaire improved significantly at the time of the final follow-up (p < 0.01). 12 months postoperatively, repair integrity was assessed by magnetic resonance imaging, which revealed that 16 patients had a type-I repair; 2 patients had a type II repair, while only 1 patient had type III repair. As per this study Re tear rate was 5% for large and massive tears. The shoulders with a type-III repair demonstrated significantly inferior functional outcome in terms of overall scores and strength compared with the other types of repairs (p< 0.01). Conclusion: In this study, we found arthroscopic double row repair technique is an effective procedure in terms of massive rotator cuff tears repair with very little risk of re-tear and significant improvement in functional activities.